Direct measurement of lifetime of transitional structures in low reynolds number pipe flows - Nishi, Mina; Ertunc, Özgür; Delgado, Antonio (6th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2009, 2009)
The lifetime of transitional flow structures in low Reynolds number pipe flows, namely puffs, was directly measured by measuring pressure drop transients in the pipe, which occur due to the generation and existence of a single transitional flow structure in the pipe. Transitional structures were generated by disturbing the flow with an iris diaphragm, which blocked the fully developed laminar flow with a certain blockage ratio and duration. Simultaneous to pressure measurements, measurements of velocity were conducted at the exit of the pipe by a hot-wire anemometry. Pipes having lengths of 200, 300 and 566 pipe diameters were employed. Pressure measurements allowed the direct determination of the lifetime of a puff, only when it dissipates in the pipe. The velocity measurements allow to determine the structure of single puffs and used to evaluate the probability of puff occurrence (survival) at the end of the pipe. The investigations of lifetime exhibited three possible routes for the development and/or the dissipation of puffs with increasing Reynolds number: Up to Re ≈ 1880, the disturbed structures develop into puffs then dissipate. After that Reynolds number, some of the puffs started to sustain remarkably longer within the pipe and some of them reaches to the end of the pipe before they dissipate. Within a very narrow Re range around 1500, the life of transitional structures was observed to remain constant. The directly measured lifetime in the range 1600 ≤ Re ≤ 1880 revealed a divergence of lifetime at Re ≈ 2300. It is demonstrated that disturbance amplitude and duration do not influence the directly measured lifetime, whereas they influenced the probability of occurrence of the puffs at the exit of the pip
Keywords: Couette flow; Shear flow; transient growth